2017
DOI: 10.3892/mmr.2017.7490
|View full text |Cite
|
Sign up to set email alerts
|

Transfection with Livin and Survivin shRNA inhibits the growth and proliferation of non-small cell lung cancer cells

Abstract: Lung cancer is reported to be a major public health issue worldwide and the overall prognosis of patients remains poor. The expression levels of Livin and Survivin, of the inhibitors of apoptosis (IAP) family, are associated with prognostic significance in the majority of solid tumors. Therefore, in the presents study, short hairpin (sh)RNA expression vectors inhibiting the Livin and Survivin genes were constructed to examine the effects of the transfection of Livin shRNA and/or Survivin shRNA on the biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Survivin silencing resensitized A549/VCR cells to vincristine and methotrexate in vitro [ 34 ]. Inhibition of survivin expression by the short hairpin RNA expression vector significantly reduced the growth of lung cancer cells in vivo and in vitro [ 35 ]. In addition, studies have shown that the polymorphisms of survivin-31 G/C and 9194 A/G are related to the risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin silencing resensitized A549/VCR cells to vincristine and methotrexate in vitro [ 34 ]. Inhibition of survivin expression by the short hairpin RNA expression vector significantly reduced the growth of lung cancer cells in vivo and in vitro [ 35 ]. In addition, studies have shown that the polymorphisms of survivin-31 G/C and 9194 A/G are related to the risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that apoptosis is regulated by multiple genes. Survivin, as a member of the IAP (apoptosis inhibiting protein) family overexpressed in various tumours, is one of the strongest apoptosis inducers [3]. Proliferation of cancer cells is promoted by survivin through direct inhibition of the activity of caspase-3 and/or caspase-7 or through prevention of mitochondria releasing cytochrome C, which could in turn inactivate the caspase.…”
Section: Introductionmentioning
confidence: 99%